2017
DOI: 10.1111/jcmm.13260
|View full text |Cite
|
Sign up to set email alerts
|

YB‐1 orchestrates onset and resolution of renal inflammation via IL10 gene regulation

Abstract: The Y‐box‐binding protein (YB)‐1 plays a non‐redundant role in both systemic and local inflammatory response. We analysed YB‐1‐mediated expression of the immune regulatory cytokine IL‐10 in both LPS and sterile inflammation induced by unilateral renal ischaemia–reperfusion (I/R) and found an important role of YB‐1 not only in the onset but also in the resolution of inflammation in kidneys. Within a decisive cis‐regulatory region of the IL10 gene locus, the fourth intron, we identified and characterized an oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…Furthermore, half-maximal expression of YB-1 led to diminished IL-10 expression upon LPS challenge, consistent with the results of a previous study [6]. However, higher YB-1 expression enhanced IL-10 mRNA expression [10]. Therefore, YB-1 exhibits both pro- and anti-inflammatory properties via IL10 gene regulation.…”
Section: Yb-1 and Akisupporting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, half-maximal expression of YB-1 led to diminished IL-10 expression upon LPS challenge, consistent with the results of a previous study [6]. However, higher YB-1 expression enhanced IL-10 mRNA expression [10]. Therefore, YB-1 exhibits both pro- and anti-inflammatory properties via IL10 gene regulation.…”
Section: Yb-1 and Akisupporting
confidence: 81%
“…Regulatory T cell-derived IL-10 plays an important renoprotective role in murine models of ischaemia-reperfusion (I/R) [24]. However, Wang et al [10] found that mice with half-maximal expression of YB-1 (Yb1 +/- ) exhibited an ameliorated inflammatory response and kidney damage at the earlier stages (days 1 and 5) of I/R with aggravated kidney injury, inflammation, and less regeneration at later stages (day 21). Moreover, YB-1 was phosphorylated at serine 102 localised to the fourth intron, the IL10 gene locus, which was paralleled by enhanced IL-10 mRNA expression in mice following lipopolysaccharide (LPS) challenge and I/R.…”
Section: Yb-1 and Akimentioning
confidence: 99%
See 1 more Smart Citation
“…YB‐1 is important in modulating inflammatory pathways including both pro‐ and anti‐inflammatory pathways, as well as repair (Hanssen et al, ; Wang et al, ). Transient upregulation of YB‐1 occurs in kidney and in heart recovering from ischemia‐reperfusion (I/R) injury during the acute phase of inflammation in experimental inflammation models.…”
Section: Discussionmentioning
confidence: 99%
“…This in vivo regulation is achieved by fusing the transgene product with a destabilizing domain, which makes the fusion protein unstable and prone to proteasome degradation; degradation can be avoided by treatment with TMP ligand. YB-1 is important in modulating inflammatory pathways including both pro-and anti-inflammatory pathways, as well as repair (Hanssen et al, 2013;Wang et al, 2017). Transient upregulation of YB-1 occurs in kidney and in heart recovering from ischemia-reperfusion (I/R) injury during the acute phase of inflammation in experimental inflammation models.…”
Section: Discussionmentioning
confidence: 99%